2018
DOI: 10.1038/s41419-018-1170-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA UCA1 promotes tumor metastasis by inducing miR-203/ZEB2 axis in gastric cancer

Abstract: Increasing studies showed that long-noncoding RNAs (lncRNAs) play important roles in the biological processes, including cancer initiation and progression. However, little is known about the exact role and regulation mechanism of lncRNA UCA1 during the progression of gastric cancer (GC). In this study, we found that UCA1 was aberrantly elevated in gastric cancer tissues, and was significantly associated with lymph node metastasis and TNM stage. In vivo and in vitro, enforced UCA1 level promoted cell migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 48 publications
3
54
0
Order By: Relevance
“…Yang et al 32 found lncRNA FTX promoted colorectal cancer progression via sponge miR‐215. Gong et al 33 observed that lncRNA UCA1 acted as a ceRNA to regulate expression of ZEB2 in gastric cancer. However, as an emerging lncRNA, the biological function of CERS6‐AS1, especially in breast cancer, is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 32 found lncRNA FTX promoted colorectal cancer progression via sponge miR‐215. Gong et al 33 observed that lncRNA UCA1 acted as a ceRNA to regulate expression of ZEB2 in gastric cancer. However, as an emerging lncRNA, the biological function of CERS6‐AS1, especially in breast cancer, is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…UCA1 could significantly promote cell migration and inhibit apoptosis in GC cell lines SUN-216 and SGC-7091 via inhibition of miR-182, whose downstream target is tissue inhibitors of metalloproteinase 2 (TIMP2) [63]. Similarly, UCA1 enhanced the invasion of GC by directly interacting with miR-203 or miR-7-5p, increasing the release of miR-203-targeted transcripts zinc finger E-box-binding homeobox2 (ZEB2) or miR-7-5p-targeted epidermal growth factor receptor (EGFR), respectively [64,65]. Moreover, UCA1 also could promote the proliferation and invasion of GC through sponging miR-495-3p [30].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…Several lncRNAs have been documented to participate in various biological processes, especially in tumorigenesis 6–8 . Multiple lncRNAs have been reported to regulate cell proliferation, migration, invasion, and apoptosis in GC cells, such as GHET1, HOTAIR, UCA1, and CASC15 among others 9–12 . LncRNAs can act as oncogenes or tumor suppressors in GC.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Multiple lncRNAs have been reported to regulate cell proliferation, migration, invasion, and apoptosis in GC cells, such as GHET1, HOTAIR, UCA1, and CASC15 among others. [9][10][11][12] LncRNAs can act as oncogenes or tumor suppressors in GC.…”
Section: Introductionmentioning
confidence: 99%